Tanda-tanda Kemunafikan dalam Prespektif Hadis: Studi Takhrij dan Syarah Hadis - Hanifatul Auliya (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about hypocrisy. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the characteristics of hypocrites in the history of Darimi No. 100. The results and discussion of this study indicate that the status of the hadith is of authentic quality because it does not have negative comments. This research concludes that the hadith narrated by Darimi No. 100 relevant points are used as motivation and a reminder to avoid hypocrisy.